2021
DOI: 10.3389/fcell.2021.682002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CDK2-Related Immune Forecast Model and ceRNA in Lung Adenocarcinoma, a Pan-Cancer Analysis

Abstract: BackgroundTumor microenvironment (TME) plays important roles in different cancers. Our study aimed to identify molecules with significant prognostic values and construct a relevant Nomogram, immune model, competing endogenous RNA (ceRNA) in lung adenocarcinoma (LUAD).Methods“GEO2R,” “limma” R packages were used to identify all differentially expressed mRNAs from Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases. Genes with P-value <0.01, LogFC>2 or <-2 were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 87 publications
0
54
0
Order By: Relevance
“…To narrow down the number of “candidate” DEGs and determine potential “key” genes for HCC development [ 30 , 31 , 33 , 34 ], a PPI network of 145 DEGs was constructed to visualize the relationships between genes, followed by functional analysis. Based on their connectivity level, the top ten hub genes identified included CCNB1, MAD2L1, CCNA2, AURKA, ZWINT, HMMR, TPX2, EZH2, and OIP5.…”
Section: Discussionmentioning
confidence: 99%
“…To narrow down the number of “candidate” DEGs and determine potential “key” genes for HCC development [ 30 , 31 , 33 , 34 ], a PPI network of 145 DEGs was constructed to visualize the relationships between genes, followed by functional analysis. Based on their connectivity level, the top ten hub genes identified included CCNB1, MAD2L1, CCNA2, AURKA, ZWINT, HMMR, TPX2, EZH2, and OIP5.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that hsa-miR-1269a had the most target genes among the 13 high-expression miRNAs, including NEGR1 , ITGA8 , CLDN18 , JAM2 , and JAM3 , associated with cell adhesion. Cell adhesion molecules are a type of membrane surface glycoprotein molecules involved in regulating inflammatory response and promoting the metastasis of LUAD ( Liu et al, 2021 ). Loss of cell adhesion is one of the characteristics of epithelial-to-mesenchymal transition (EMT), and the low expression of adhesion molecules is associated with distant metastasis in LUAD ( Kim et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…To further verify the prediction power of our risk score, we performed stratified analysis by clinical classifications. We built the nomogram on the basis of the outcomes of multivariate Cox regression to predicting 1-, 3-, and 5-year survival probability through “rms” package ( 29 ). The calibration figures represent the consistency of our prediction with reality.…”
Section: Methodsmentioning
confidence: 99%